Pengaruh Struktur Kepemilikan Dan Struktur Modal Terhadap Nilai Perusahaan(Studi pada Perusahaan Real Estate And Properti Yang Listing di Bursa Efek Indonesia tahun 2010-2014) - Widowati, Sinta Dewi; , Dra.Wuryaningsih Dwi Lestari,MM (2016)
The of this study was to analyze the effect of partially or simultaneously managerial ownership, institutional ownership and capital structure on firm value (Studies in Corporate Real Estate and Property in Indonesia Stock Exchange 2010-2014). The method used in this research is descriptive method and verification with quantitative approach. The population is all companies Real Estate and Property listing in BEI period 2010-2014 totaling 50 companies. The samples in this study using purposive sampling technique acquired 27 companies in the sample. Analysts tool used classical assumption test (Test Normality, Multicollinearity Test, Test and Test Heteroskidastity autocorrelation) and Multiple Linear Regression Analysis, Testing hypotheses (t-test), hypothesis testing (test-f) and the coefficient of determination R2. Results of data analysis obtained results: managerial ownership significant negative effect on the value of the company. Institutional ownership has significant negative effect on the value of the company. Capital Structure not significant effect on the value of the company. And the F test showed that managerial ownership, institutional ownership and capital structure simultaneously significant effect on the value of the company (Studies in Corporate Real Estate and Property in Indonesia Stock Exchange 2010-2014).